Publisher Correction: Chloroquine modulates antitumor immune response by resetting tumor-associated macrophages toward M1 phenotype - Degao Chen (Nature Portfolio, 2018)
In the originally published version of this Article, images in Fig. 5n were inadvertently replaced with duplicates of images in Fig. 5o during the production process. This has now been corrected in both the PDF and HTML versions of the Article.